2017 world state of quality: first worldwide results. (17th February 2021) - Cubo, Catarina; Saraiva, Pedro; Sampaio, Paulo; Reis, Marco
Abstract : To measure country quality performance we propose to use sixteen indicators divided into ten dimensions that compose the World State of Quality (WSQ) model. Here we will describe the first worldwide application of this model, which was previously piloted over European Union countries. For that purpose, we are now covering one hundred and ten countries, grouped according to five categorises of overall quality performance (Leading, Follower, Moderate, Lagging, and Beginning). This overall quality performance is computed based on the ranking positions achieved by each country and for each indicator. Statistical data analysis was also carried out, leading to the identification of similar country quality profiles and the identification of a diversity of ways that are being adopted by different countries to pursue their quality journey. Following this approach, the characterisation of countries in terms of quality strengths and improvement areas can be also achieved, according to the corresponding country quality profiles obtained for the one hundred and ten countries studied.